Penerapan Asas Kontradiktur Delimitasi di Kantor Pertanahan Kota Jayapura - Sahuleka, Onesimus; Manengkey, Victor Th; Katjong, Kadir; Tanati, Daniel; Palenewen, James Yoseph (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research aims to determine the application of the principle of delimitation contradiction at the Jayapura City Land Office and to determine the resolution of land disputes resulting from the non-implementation of the principle of delimitation contradiction at the Jayapura City Land Office. The research method used is normative juridical and empirical, namely an approach that refers to statutory regulations, library materials, written regulations or other secondary legal materials and looks at their application through field research. The results of this research reveal that the application of the Delimitation Contradiction Principle at the Jayapura City Land Office can actually work well, but if it is related to technical problems in previous maps such as old registration maps that have been lost or have been damaged, there are often overlaps or overlapping plots of land and also what often happens in the field is that the bordering party is not present so BPN entrusts a sheet to fill in the measuring drawings, automatically this is where the application of the Delimitation Contradictory Principle does not work properly and the resolution of land disputes due to not implementing the Delimitation Contradiction Principle is where the BPN facilitates mediation between the two parties rather than having to go to court. If it is still not resolved, a procedural team is created whose members are from the structural work unit in accordance with the procedures for handling land disputes regulated in the Minister of State for Agrarian Affairs/KBPN Regulation No. 5 of 1999. The task of the work team is to receive and resolve land disputes that come to local work environment. So that the resolution of land disputes does not necessarily take place directly through litigation.